2006
DOI: 10.1007/s11552-006-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Fingertip Reconstruction with the Laterally Based Thenar Flap: Indications and Long-Term Functional Results

Abstract: The thenar flap is a time-tested method of fingertip reconstruction, but functional outcome data are scarce in the literature. The purpose of this study was to analyze the long-term function following fingertip reconstruction with a laterally based thenar flap and to compare these results with other established methods. Nineteen patients underwent a thenar flap between 2001 and 2004. Patients ranged in age from 3 to 48 years. The mean angle of proximal interphalangeal immobilization was 66 degrees (range 30-85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In a study of 150 patients, Melone et al 6 described that modified thenar flap based laterally have shown excellent results. In 2006, Rinker 7 published a study of 19 patients that he used the lateral thenar flap for fingertip reconstruction and reported good functional and aesthetic recovery with minimal complications.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 150 patients, Melone et al 6 described that modified thenar flap based laterally have shown excellent results. In 2006, Rinker 7 published a study of 19 patients that he used the lateral thenar flap for fingertip reconstruction and reported good functional and aesthetic recovery with minimal complications.…”
Section: Introductionmentioning
confidence: 99%
“…Rinker evaluated 17 thenar flaps (only 3 in patients over age 45 years) after an average of 20 months. 20 He found no proximal interphalangeal joint contractures in the group but a notable decrease in DIP joint range of motion. Mean static 2-point discrimination was 6.8 mm in the reconstructed fingertips versus 3.8 mm in the uninjured contralateral digits.…”
Section: The Evidencementioning
confidence: 86%
“…To obtain adequately sized flaps for both fingertips, we used an ulnar-or radial-based extended thenar flap technique, and the donor site defect was grafted with the skin harvested from the medial aspect of the foot. Melon et al 16 noted that ulnar-or radial-based thenar flaps are used for specific situations, especially loss of exceptionally large pulp portions, and previous studies have focused on the application of radial- 19,20 and ulnar-based thenar flaps 21 in single fingertip amputations. With our technique, we found that wide flap harvest of up to 4-5 cm in length and up to 2.5-3 cm in width could possibly cover the defects of both fingers.…”
Section: Discussionmentioning
confidence: 99%